Antioxidant Activity of a Combination of Pegagan (Centella asiatica) and Temulawak (Curcuma xanthorrhiza) Rhizomes Using the DPPH Method - Dewi Kurnia; Mae Maelani; Asep Roni (PT CENDEKIA SCIENCE AND TECHNOLOGY, 2025)
Pegagan (Centella asiatica) and temulawak (Curcuma xanthorrhiza) rhizomes are plants commonly recommended for enhancing the body's immune system. This study aimed to evaluate the antioxidant activity of extracts from pegagan, temulawak, and their combination to determine if a synergistic effect exists between the two extracts. Extraction was performed using the maceration method with 70% ethanol as the solvent. The yield of the pegagan herb extract was 20.96%, while the temulawak rhizome extract yielded 10.88%. For preliminary testing, thin-layer chromatography (TLC) was used to analyze the samples in various mobile phases, including the polar chloroform:methanol:water (7:2:0.15), non-polar n-hexane:ethyl acetate (6:5), and semi-polar chloroform:methanol (9:1). The results indicated the presence of flavonoids, phenols, and 0.2% DPPH. Antioxidant activity was measured using UV-Vis spectrophotometry at a wavelength of 516 nm with the DPPH method. The antioxidant activity results showed that the pegagan extract alone had an IC50 of 96.109 µg/mL, the temulawak extract alone had 94.151 µg/mL, and the combinations had IC50 values of 41.884 µg/mL (1:1), 71.074 µg/mL (1:2), and 26.335 µg/mL (2:1). Based on these results, both single and combined extracts exhibited antioxidant activity, with the combination showing higher activity and a synergistic effect.